Avian Influenza (H5N1) Susceptibility and Receptors in Dogs - Riks Maas; Mirriam Tacken; Lisette Ruuls; Guus Koch; Eugene van Rooij; Norbert Stockhofe-Zurwieden (Emerging Infectious Diseases, 2007)
Inoculation of influenza (H5N1) into beagles resulted in virus excretion and rapid seroconversion with no disease. Binding studies that used labeled influenza (H5N1) showed virus attachment to higher and lower respiratory tract tissues. Thus, dogs that are subclinically infected with influenza (H5N1) may contribute to virus spread.